(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objectives: Antimicrobial resistance is one of the growing public health problems in developing countries like Pakistan. Therefore, this study aimed to determine the type of microorganisms acquired by newborns immediately after birth and the antimicrobial resistance patterns of the bacteria isolated from eye swab samples. Methods: Women were recruited from the Obstetrics ward of two tertiary care hospitals in Karachi, Pakistan. Immediately after birth conjunctival swabs were taken from one eye of the newborn. The information like mode of delivery, person conducted delivery, gestational age, and birth weight was noted from hospital records. Results: From 203 eye swabs collected, microbial growth was observed in 69 (34 % with 95 % confidence interval CI: 27.48% - 40.52%). Gram-positive bacteria were observed in 16 (23.2%) and Gram-negative bacteria were found in 50 (72.5%) and yeast was also seen in 3 (4.3%). The most common gram-positive organisms observed were Staphylococcus species in 16 swabs (20.3%) and E. coli in 20 (25.3%), followed by Acinetobacter species in 10 (12.7%), Enterobacter species in 8 (10.1%), Pseudomonas stutzeri in 6 (7.6%), Pseudomonas species in 6 (7.6%) and Pseudomonas aeruginosa in 4 (5.1%). All 4 (100%) Pseudomonas aeruginosa strains were resistant to Augmentin and Cotrimoxazole and from 16 Staphylococcus species, 87.7% were resistant to Penicillin, 56.3% to Erythromycin, 50% to Cloxacilinn, 43.7% to Tetracycline, 31.3% to each Cotrimoxazole, Fusidic acid, Gentamycin. Conclusions: The carriage of antimicrobial-resistant bacteria immediately after birth is high in the newborn of the lower middle-class population of Karachi. Raising awareness regarding the intake of antibiotics on prescription can also reduce the risk to the newborn baby and the mother.